Assembly of Optimum Habitats for Asian Houbara Bustard (Chlamydotis macqueenii) in the Arabian Peninsula: The Vegetation Aspects. (24th June 2015) - Asadalla, Naseraldeen Baqer; Abido, Mohammad Sulaiman; Abahussain, Asma; Shobrak, Mohamed
Abstract : This research was conducted in four sites at Mahazat as-Sayd reserve in Saudi Arabia to determine the optimum habitats' constituents for Asian houbara bustard Chlamydotis macqueenii via assessing abiotic and biotic factors with special reference to vegetation aspects. Vegetative parameters were quantified using combinations of distance and line intercept methods. Acquired data were analyzed using cluster analysis and analysis of variance tests. Results indicated that three of the four plant communities of the study sites were dominated by Acacia tortilis with underground cover composed of lesser species. On the other hand, White Jabal was dominated by scrubs composed mainly of Fagonia indica with sparse Acacia trees. Rumrumiyya site recorded the highest species abundance and vegetative coverage (133%) among the sites. It is concluded that Black Jabal and White Jabal sites are used as nesting and foraging habitats for houbaras, whereas Jabal Khurse is specifically a males' display site. Nevertheless, Rumrumiyya site was used for foraging and shelter. The study confirmed that density and vegetation cover are of prime importance for houbara site selection. However, other factors affecting feeding and behavior of the species must be considered in further studies.